A Comparison of Success Rates in Ultrasound Guided Subclavian Vein Cannulation through Supraclavicular and Infraclavicular Approach: A Randomised Trial - Gayathri Shankar , Karthik Mani , Gokulakrishnan C (South Eastern European Journal of Public Health, 2025)
Introduction: In intensive care units (ICUs), central venous catheterisation (CVC) is crucial for administering drugs, supplying fluids, and tracking haemodynamics. In critically sick adult patients in India, this study compares the efficacy of infraclavicular (IC) and supraclavicular (SC) ultrasound-guided methods for subclavian vein cannulation. Methodology: A prospective randomized controlled trial was carried out at SRM Medical College Hospital & Research Centre from August 2022 to August 2024. A total of 100 ICU patients were randomly assigned to either the SC or IC group. The study analyzed key variables such as total procedure time, venous visualization time, venous puncture time, number of attempts, catheterization time, and complications. Data analysis was performed using SPSS version 21, with statistical significance defined as p < 0.05. Results: In the study, the mean age of patients in the SC group was 41.58±15 years, compared to 44.2±12.3 years in the IC group, with similar gender distributions across both groups. Procedural metrics revealed that the SC group had a significantly shorter total procedure time (174.1±12.7 minutes) compared to the IC group (213.3±24.2 minutes) (p < 0.001). The SC group also achieved faster venous visualization (45±16.3 minutes) compared to the IC group (62.3±16.8 minutes) (p < 0.001). Venous puncture time was shorter in the SC group (33.8±4.2 minutes) than in the IC group (43.1±4.3 minutes) (p < 0.001). Additionally, the SC group required fewer attempts (1.4±0.5) compared to the IC group (2±0.9) (p < 0.001) and had a shorter total access time (5.6±1.3 minutes) versus the IC group (8.2±2.8 minutes) (p < 0.001). The IC approach was associated with higher complication rates, including arterial puncture and catheter malposition. Discussion: Significant benefits were seen between the SC and IC approaches: shorter procedure durations, faster venous visualisation and puncture, fewer failed attempts at successful catheterisation, and shortened access times. These results imply that the SC method is safer and more effective. Conclusion: For critically sick patients, the SC method to subclavian vein cannulation offers significant advantages in terms of effectiveness, success rates, and decreased complications. The SC strategy, which has the potential to enhance patient outcomes, is supported by this study as the recommended CVC technique in intensive care units. It is recommended to do further studies to confirm these results.